Vildagliptin and its role in the treatment of diabetes mellitus - Yury Shavkatovich Khalimov (Сахарный диабет)
Type 2 diabetes mellitus is a most serious medical problem throughout the world. Traditional hypoglycemic agents do not ensure long-term control ofglycemia and fail to affect the natural course of DM. An ideal hypoglycemic medicine must be efficacious, safe, and convenient to use for the preventionof progressive deterioration of beta-cell function during prolonged therapy; also, it should have positive effect on the outcome of DM. The use of incretinsin the recent decade is a new promising approach to the management of DM2. The group of incretins includes gastrointestinal hormones released inresponse to food intake to stimulate insulin secretion. Dipeptidyl peptidase-4 (DPP-4) inhibitors, a new class of hypoglycemic agents, have been inuse in this country for over 3 years. Vildaglyptin (Galvus) is a representative of DPP-4 inhibitors and GalvusMet is the sole combination of DPP-4inhibitor with metformin registered in Russia. The advent of incretin mimetics necessiatate revision of national and international guidelines for DM2therapy. Results of international clinical studies show that Galvus and GalvusMet are efficacious and safe, they ensure adequate control of glycemiafree from complications and side effects. An important advantage of these preparations is the possibility of their use by elderly patients with arterialhypertension and moderate renal dysfunction and by those at risk of cardiovascular disorders. The evidence-based Galvus information is highly convincing.The advantages of Galvus over traditional agents give reason to recommend it as a medicine of choice for the initiation of DM2 therapy. Approvedcombinations of Galvus with other hypoglycemic agents may be used at all stages of intensive therapy of DM2.